2021
DOI: 10.1002/ijc.33893
|View full text |Cite
|
Sign up to set email alerts
|

Impact of specific high‐risk human papillomavirus genotypes on survival in oropharyngeal cancer

Abstract: The increases observed in incidence and survival of oropharyngeal squamous cell carcinoma (OPSCC) have been attributed to human papillomavirus (HPV) infection, but the survival‐impact of specific genotypes is poorly understood. We investigated the potential influence of HPV genotypes on survival in HPV‐positive (HPV+) OPSCC. All patients with HPV+/p16+ OPSCC and available genotype data within the period 2011 to 2017 in Eastern Denmark were included. Descriptive statistics on clinical and tumor data, as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…In future, it may add value in relation to liquid biopsies with cell-free HPV DNA in the follow-up surveillance after treatment [ 10 ]. A recent study has investigated the role of high-risk HPV genotypes on survival in patients with oropharyngeal cancer, and found no differences when comparing HPV16 with non-HPV16 genotypes [ 11 ]. The subgroup analysis indicated that the group of patients with genotypes HPV33 and HPV35 has a significantly better 5-year overall survival than other non-HPV16 genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…In future, it may add value in relation to liquid biopsies with cell-free HPV DNA in the follow-up surveillance after treatment [ 10 ]. A recent study has investigated the role of high-risk HPV genotypes on survival in patients with oropharyngeal cancer, and found no differences when comparing HPV16 with non-HPV16 genotypes [ 11 ]. The subgroup analysis indicated that the group of patients with genotypes HPV33 and HPV35 has a significantly better 5-year overall survival than other non-HPV16 genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…HPV infection can be classified into P16+/HPV+, p16+/HPV−, or p16−/HPV+. Some studies have reported that the OS of p16+/HPV− and p16−/HPV+ are poor ( 37 ). However, the included studies in this meta-analysis failed to distinguish between these three specific categories, and thus, we could determine whether our results were affected by HPV status in the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Although the natural history of the transition to oropharyngeal cancer is not fully clarified, it is now commonly accepted that a subclinical oral HPV infection persisting for 10–30 years is an obligate precursor of the majority of OPSCCs [ 12 , 13 , 16 ] Indeed, HPV detection in OPSCCs increased dramatically over time and several high-risk types have been identified, including 16 and 18, 31, 33, 35, 52, 58 (all genetically related to HPV 16); and 39, 45, 59 (genetically related to HPV 18), with HPV 16 accounting for 70–80% of cases [ 17 , 18 ].…”
Section: Epidemiological Background Of Oropharyngeal Hpv Infectionmentioning
confidence: 99%